A Thematic Commentary on the Qur’an: By Muhammad al-Ghazali (Virginia: The International Institute of Islamic Thought, 2000. 804 pages.) (American Journal of Islam and Society, 2003)
There has been an increasing interest in the Qur’an’s literary aspects withinthe field of Qur’anic studies over the last few years. In the past, westernscholars have devoted a great deal of energy to tracing foreign influencesin the Qur’an or reconstructing the chronology of its verses and surahs.However, the trend now is shifting toward textual studies, a developmentindicated by the proliferation of articles, anthologies, and books on theQur’an as a composed literary ornament.This shift is both refreshing and welcome, particularly for those whoare more interested in understanding the Qur’an in its present form, ratherthan learning about its textual history or compilation. Classical Islamicscholarship developed a body of exegetical material on the Qur’an’s miraculousnature (i‘jaz) from a literary perspective. This approach has taken aprimarily microscopic linguistic viewpoint (balaghah [eloquence]) ofstudying the choice of words and how the verses are constructed.Although it has always been accepted that the Qur’an’s surahs are distinctliterary pieces with their own style and content, comprehensive attemptsto present entire surahs as thematically independent entities have been rare.With increasing pressure from western scholars that the Qur’an is incoherentand haphazardly arranged, a new genre of exegetical material is developing,both in Muslim and western circles. This new genre focuses upon explainingwhy the surah should be considered as a distinctly composed piece with itsown dynamic of sound and meaning. Muhammad al-Ghazali’s work fallswithin this emerging category of Qur’anic exegesis.A Thematic Commentary on the Qur’an is a translation from al-Ghazali’s Al-Tafsir al-Mawdu‘i. The print is well typeset and easily legible,not cramped together, with a glossy green cover commanding an elegance ...